海洋性小型歯鯨(スジイルカ)の成体,乳児,胎児の組織および器官における分枝鎖脂肪酸の分布 - Morii, Hideaki (長崎大学水産学部, 1980)
The fatty acid composition of lipids in the subcutaneous tissue, muscle and organs such as the liver of the adult, nursling and foetus whales, Stenella caeruleo-alba was studied. In the adult and nursling, short- and long-chain branched acids (including both iso and anteiso acids) were contained also in the muscle (body part) and organs in addition to the adipose tissue (muscle of jaw and melon parts and subcutaneous tissue). However, the acids in the muscle and organs were much less than those in the adipose tissue, and their compositions in the former differed from that in the latter. Especially, the long-chain branched acid composition in the muscle and organs was rather similar to that of fish oil. On the other hand, a fair amount of the branched-chain acids existed in the tongue and gall-bladder of the adult and nursling and in the stomach of the nursling, and thier compositions also were similar to that in the adipose tissue. In the foetus, the lipid content in the melon and jaw (corresponding to the adipose tissue in the adult and nursling) was less than 1.0% and the branched-chain acids also were scanty, although they were more than in the muscle and organs. The relative content of short- and long-chain branched acids in various kinds of adipose tissue was almost similar in both the adult and nursling. 成体,乳児,胎児イルカの各皮下組織,筋肉,肝臓などの諸器管の脂質の低級および高級酸組成をしらべた.成体と乳児では,脂肪組織(顎部およびメロン体部の筋肉と皮下組織)のほか,筋肉(体部)や肝臓などの諸器管にも低級および高級分枝酸(イソおよびアンテイソ酸の双方を含む)が存在した.しかしながら,筋肉や肝臓などの諸器管では分枝酸は少なく,組成も脂肪組織と異なり,高級分枝酸に至っては魚油に類似していた.ところが,成体と乳児の舌,胆のうおよび乳児の胃にはかなり多量の分枝酸が存在し,その組成も脂肪組織のものと似ていた.胎児のメロン体と顎皮(成体および乳児では脂肪組織)の脂質量は1%以下で,分枝酸も少なかった.しかしながら,分枝酸は筋肉や肝臓などの諸器管以上に含まれていた.成体,乳児とも,各種脂肪組織の低級分枝酸量と高級分枝酸量の大小関係はほぼ似ていた. 長崎大学水産学部研究報告, v.49, pp.35-52; 1980 departmental bulletin paper